2008
DOI: 10.1645/ge-1297.1
|View full text |Cite
|
Sign up to set email alerts
|

Response of Schistosoma mansoni Isolates Having Different Drug Sensitivity to Praziquantel Over Several Life Cycle Passages with and Without Therapeutic Pressure

Abstract: The stability of praziquantel (PZQ)-insusceptible S. mansoni isolates and the possible selection of PZQ-insusceptible parasites upon applying therapeutic pressure were examined over several life cycle passages (snails to mice). To test isolate stability, 3 PZQ-susceptible and 7 PZQ-insusceptible isolates were used to establish infection in mice, and they were passaged each for 2-5 life cycles. After each passage, 6 groups of mice were used to assess the PZQ dose at which the worm burden was decreased by 50% (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 23 publications
1
21
0
Order By: Relevance
“…Collaborative experiments performed in independent laboratories in Italy, Egypt and the UK, using standard-operating procedures to estimate the ED 50 s of S. mansoni isolates that were putatively resistant and sensitive to PZQ, confirmed that different isolates of this species do seemingly have varied sensitivities to PZQ [85]. Further tests on the stability of PZQ-sensitivity of some of the isolates examined in the last study have been performed more recently [86 ].…”
Section: Schistosome Resistance To Praziquantelmentioning
confidence: 67%
“…Collaborative experiments performed in independent laboratories in Italy, Egypt and the UK, using standard-operating procedures to estimate the ED 50 s of S. mansoni isolates that were putatively resistant and sensitive to PZQ, confirmed that different isolates of this species do seemingly have varied sensitivities to PZQ [85]. Further tests on the stability of PZQ-sensitivity of some of the isolates examined in the last study have been performed more recently [86 ].…”
Section: Schistosome Resistance To Praziquantelmentioning
confidence: 67%
“…8 Even though praziquantel is an effective drug for the treatment of the disease, it has been in use for more than 20 years and recent reports indicate that significant resistance to the drug may be present in different geographic locations. 9 The identification and study of novel molecular targets as well as the development of new drugs to treat this and other neglected tropical diseases are of utmost importance in drug discovery. [10][11][12] The parasite Schistosoma mansoni, one of the etiologic agents of human schistosomiasis, lacks the de novo pathway for purine biosynthesis and depends entirely on the salvage pathway for its purine requirements for synthesis of RNA and DNA.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, praziquantel has been in use for more than 20 years and significant resistance to the chemotherapy has emerged. 2 Therefore, this scenario highlights the urgent need for the development of new drugs to treat the disease. 2,3 Enzymes are attractive biological targets for smallmolecule drug discovery.…”
Section: Introductionmentioning
confidence: 99%
“…2 Therefore, this scenario highlights the urgent need for the development of new drugs to treat the disease. 2,3 Enzymes are attractive biological targets for smallmolecule drug discovery. 4,5 Purine nucleoside phosphorylase (PNP, EC 2.4.2.1) is a key enzyme in the purine salvage pathway which has been primarily studied as a target for the treatment of T-cell proliferative diseases, such as T-cell leukemias or lymphomas, organ transplant rejection, rheumatoid arthritis, psoriasis, and some other autoimmune diseases.…”
Section: Introductionmentioning
confidence: 99%